Pattern of plant communities’ influence to grasshopper abundance distribution in heterogeneous landscapes at the upper reaches of Heihe River, Qilian Mountains, China - Li, Lili; Zhao, Chengzhang; Zhao, Xiawei; Wang, Dawei; Li, Yu (Environmental science and pollution research international, 2022)
Understanding the impact of the heterogeneity of the ecological environment on biodiversity is a key issue in ecology. Topographical heterogeneity was potentially important in grassland systems to create or change habitats for grasshopper settlement and foraging. Yet, there was little knowledge of how grasshopper communities respond to plant communities along the altitude gradient. We investigated the role of plant communities on grasshopper diversity with geostatistical methods to test the effects of heterogeneity in the natural grassland on the upper reaches of the Heihe River, Qilian Mountains. To aim the goal of the study, nonreturn experiments were used to collect the grasshoppers’ diversity and populations, and the plant’s community was sampled at the same location. The results showed that the semivariograms of grasshopper abundance and plant communities were both nonlinear models, while the grasshopper abundance typically produces heterogeneity with a larger range and nuggets than plant communities (except the plant coverage range in the model, range <1.5 m). The two communities presented the spatial distribution pattern of aggregated distribution, and the spatial trend is more intense in the northeast-southwest direction than in the northwest-southeast. The grasshopper species developed a good selection on microenvironment to habitat and the distribution consistent with plants, forming the horizontal distribution with a flaky and plaque distribution pattern. The relationship between grasshoppers and plants was highly dependent on the altitude, and grasshopper abundance has a positive correlation with plant richness ( F = 0.68) and plant coverage ( F = 0.32) and has a negative correlation with plant height ( F = 0.13). In summary, the spatial distribution and correlation characteristics of plant communities and grasshoppers formed a plaque heterogeneity structure under the altitude gradients.